Efficacy of Prophylactic Antibiotic Administration for Breast Cancer Surgery in Overweight or Obese Patients A Randomized Controlled Trial - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2013)
Objective: To assess the impact of prophylactic antibiotics on the prevention of surgical site infection (SSI) and the cost-effectiveness of this prophylaxis for breast cancer surgery in overweight or obese women. Background Data: SSI is higher than expected after breast surgery. Obesity was found to be one of the risk factors. Methods: The trial was designed as a phase IV randomized, controlled, parallel-group efficacy trial. It was conducted at a tertiary university hospital. Overweight or obese women with clinically early-stage breast cancer who had been assigned to undergo surgery were eligible. Patients were randomly allocated to either a prophylaxis or a control group by using a computer-generated list. The prophylaxis group received 1 g ampicillin-sulbactam intravenously at anesthesia. The control group received no intervention. Patients and observers were blinded to the assignments. The primary outcome was the comparison of SSI incidences of the 2 groups. Patients were monitored for 30 days. Results: A total of 369 patients were included in final analysis, out of which 187 were allocated for prophylaxis and 182 were randomly assigned to the control group. Analysis was done according to the intention-to-treat principle. Prophylaxis significantly reduced the SSI rate (4.8%) in the prophylaxis group when compared with that in the control group [13.7%; relative risk (RR) 0.35; 95% CI: 0.17-0.73]. No adverse reaction was observed. The mean SSI-related cost (20.26 USD) was found to be significantly higher in the control group when compared with that (8.48 USD) in the prophylaxis group. Conclusion: Antibiotic prophylaxis significantly decreased SSI incidence after elective surgery and was shown to be cost-effective in obese breast cancer patients. ClinicalTrials.gov Identifier: NCT00356148
Keywords: ampicillin-sulbactam; antibiotic prophylaxis; breast cancer; breast surgery; obesity; SURGICAL SITE INFECTION; WOUND-INFECTION; DOUBLE-BLIND; RISK-FACTORS; MASTECTOMY; MORBIDITY; BIOPSY